(untitled) - Parsons, Keith M. (Boston, 2005)
This provocative, focused, and succinct new text addresses two issues integral to the study of the philosophy of science: the rationality of science and the realism question. Students are invited to think deeply about salient issues as they explore collections of cases and examples, beginning by considering the founding document of modern science, Copernicus’s On the Revolutions of the Heavenly Spheres, and including discussions of other key readings such as Thomas Kuhn’s The Structure of Scientific Revolutions. Author Keith Parsons challenges students’ thinking, offering his own views while providing a solid foundation for debate.
Keywords: Science,Khoa học; Philosophy,History,Triết học,Lịch sử